Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 102985 by DGmichael last updated on 12/Jul/20

Answered by mathmax by abdo last updated on 12/Jul/20

at form of serie    let f(x) =∫_0 ^x  (e^t /((1+t^2 )^2 ))dt  if o≤x<1  we  have  (1/(1+u)) =Σ_(n=0) ^∞  (−1)^n  u^(n )  ⇒by derivation we get  −(1/((1+u)^2 )) =Σ_(n=1) ^∞  n(−1)^n  u^(n−1)  ⇒(1/((1+u)^2 )) =Σ_(n=1) ^∞  n(−1)^(n−1)  u^(n−1)  ⇒  (1/((1+t^2 )^2 )) =Σ_(n=1) ^∞  n(−1)^(n−1)  t^(2n−2)   ⇒f(x) =∫_0 ^(x ) e^t (Σ_(n=1) ^(∞ ) n(−1)^(n−1 ) t^(2n−2) )dt  =Σ_(n=1) ^∞  n(−1)^(n−1)  ∫_0 ^(x ) t^(2n−2)  e^t  dt  =Σ_(n=1) ^∞  n(−1)^(n−1)  U_n   U_n =∫_0 ^x  t^(2n−2 )  e^t  dt   by parts  u^′  =t^(2n−2)  and v =e^t  ⇒  U_n =[(1/(2n−1)) t^(2n−1)  e^t ]_0 ^x  −∫_0 ^x  (1/(2n−1)) t^(2n−1)  e^(t ) dt  =((x^(2n−1)  e^x )/(2n−1)) −(1/(2n−1)) ∫_0 ^x  t^(2n−1)  e^t  dt and  ∫_0 ^x  t^(2n−1)  e^t  dt =[(t^(2n) /(2n)) e^t ]_0 ^x  −∫_0 ^x  (t^(2n) /(2n))e^t  dt =((x^(2n)  e^x )/(2n)) −(1/(2n)) ∫_0 ^x  t^(2n)  e^t  dt  =((x^(2n)  e^x )/(2n))−(1/(2n))U_(n+1)  ⇒U_n =((x^(2n−1)  e^x )/(2n−1))−(1/(2n−1)){((x^(2n)  e^x )/(2n))−(1/(2n)) U_(n+1) }  =((x^(2n−1)  e^x )/(2n−1))−((x^(2n)  e^x )/((2n−1)(2n))) +(1/(2n(2n−1))) U_(n+1)   ...be continued

atformofserieletf(x)=0xet(1+t2)2dtifox<1wehave11+u=n=0(1)nunbyderivationweget1(1+u)2=n=1n(1)nun11(1+u)2=n=1n(1)n1un11(1+t2)2=n=1n(1)n1t2n2f(x)=0xet(n=1n(1)n1t2n2)dt=n=1n(1)n10xt2n2etdt=n=1n(1)n1UnUn=0xt2n2etdtbypartsu=t2n2andv=etUn=[12n1t2n1et]0x0x12n1t2n1etdt=x2n1ex2n112n10xt2n1etdtand0xt2n1etdt=[t2n2net]0x0xt2n2netdt=x2nex2n12n0xt2netdt=x2nex2n12nUn+1Un=x2n1ex2n112n1{x2nex2n12nUn+1}=x2n1ex2n1x2nex(2n1)(2n)+12n(2n1)Un+1...becontinued

Answered by maths mind last updated on 12/Jul/20

∫(e^x /(t+x^2 ))dx=f(t)  =(1/(2i(√t)))∫{−(e^x /(x+i(√t)))+(e^x /(x−i(√t)))}dx  u=x+i(√t)⇒du=dx  =−(1/(2i(√t)))∫(e^(u−i(√t)) /u)du+(1/(2i(√t)))∫(e^(u+i(√t)) /u)du  =2Re∫(e^(u+i(√t)) /u)du  =2Re∫(e^u /u){cos((√t))+isin((√t)))du  =2∫(e^u /u)cos((√t))du=2cos((√t))E_i (u)  =2cos((√t))E_i (x+i(√t))+c=f(t)  we want−f′(1)  f′(t)=−2sin((√t))E_i (x+i(√t))+(i/(√t))cos((√t)).(e^(x+i(√t)) /(x+i(√t)))  −f′(1)=2sin(1)E_i (x+i)−((cos(1)e^x (cos(1)+isin(1)))/(x+i))+c  =∫(e^x /((1+x^2 )^2 ))dx

ext+x2dx=f(t)=12it{exx+it+exxit}dxu=x+itdu=dx=12iteuitudu+12iteu+itudu=2Reeu+itudu=2Reeuu{cos(t)+isin(t))du=2euucos(t)du=2cos(t)Ei(u)=2cos(t)Ei(x+it)+c=f(t)wewantf(1)f(t)=2sin(t)Ei(x+it)+itcos(t).ex+itx+itf(1)=2sin(1)Ei(x+i)cos(1)ex(cos(1)+isin(1))x+i+c=ex(1+x2)2dx

Terms of Service

Privacy Policy

Contact: info@tinkutara.com